Context-Based Thematic Teaching Materials to Improve Elementary Students’ Learning Achievements - Wardani, Nur Fitriana Kusuma; Sunardi, Sunardi; Suharno, Suharno (Jurnal Pendidikan Indonesia, 2020)
Contextual learning connects the content of subject matters in the classroom with the context of students’ daily lives. Elementary school learning is conducted using a thematic approach that integrates various learning contents into a theme. Thematic teaching materials in elementary schools depend on textbooks provided by the government and are limited in number. Therefore, this study aims to develop context-based thematic teaching materials to improve the learning achievements of elementary school students. In this study, the research and development method was used with the 4D model (Define, Design, Develop, and Disseminate). The product of development was validated by experts. Testing of the product was conducted twice, namely a small-group test with 8 elementary school students grade IV in SD 2 Guwo and a large-group t to determine the effectiveness of the teaching material developed. The large-group test involved 32 students of grade IV in SD Negeri 2 Kadipaten as the experimental class and 30 students of grade IV in SD Negeri 2 Guwo as the control class. The results of this study indicate that there are significant differences in learning achievements between the experimental class and the control class. The experimental class using context-based thematic teaching materials has better performance than the control class using thematic textbooks. The context-based thematic teaching material that has been developed has been proven to be able to improve student achievement. The results of this study are expected to be a reference for teachers and policymakers to develop context-based thematic teaching materials.